Developing a Treatment Protocol for Shark Attack Victims: A Systematic Review - Matthew Levenson (Medical Science: Trends and Innovations Vol. 7, 2025)
Shark attacks are a multifactorial rare traumatic event that makes headlines globally. However, shark attacks increased by 23% across the globe within the past 20 years on a multifactorial scale driven by climate change and human impacts, yet healthcare lacks treatment guidelines for these victims. Although shark attacks are rare, treatment consists of standard trauma guidelines, such as transfusions, standard labs, diagnostic imaging, and prophylactic antibiotics. This systematic review proposed a shark attack treatment protocol that will potentially reduce the morbidity and mortality rates by assessing prehospital management with transfusions, hospital management with prophylactic antibiotics, and mental health evaluations to prevent and/or treat psychological impacts. Two databases were used, Access Medicine and Google Scholar. This study screened 463 sources and eliminated 432 sources due to repetition or irrelevance to this study. The review revealed that shark attack victims have a greater risk of hypovolemic shock and hypothermia. Treatment should be immediately initiated. Due to the lack of emergency medical service guidelines for blood transfusions, a protocol has been proposed. The protocol initiates with prehospital management by implementing EMS to follow the SHARC protocol (systolic blood pressure (SBP) < 90, hemorrhage, appearance, radius of the bite over 15 cm, and coagulopathy) to administer whole blood transfusions in route to a hospital to prevent hypovolemic shock. The next step is the antibiotic protocol to administer ciprofloxacin or moxifloxacin, and a third-generation cephalosporin with doxycycline to prevent wound infections commonly caused by vibrio species. Assessing mental health before and three months after discharge can help prevent and/or treat anxiety, depression, and post-traumatic stress disorder (PTSD). Future directions should include clinical trials to quantify the effectiveness of the protocol proposed in this study in comparison to existing care strategies.